Analisis Kritis Terhadap Preferensi Akad Jual Beli Atas Bagi Hasil di Perbankan Syariah: Studi Kepustakaan Tentang Karakteristik Risiko dan Implikasi Kinerja - Nikmatullah Nur; Ilyas; Asriadi (Al Rikaz: Jurnal Ekonomi Syariah, 2026)
This descriptive qualitative library research aims to comparatively examine the theoretical concepts and practical implementation of sale-based and profit-sharing contracts in modern Islamic banking. Secondary data consisting of regulations and scientific journal articles published between 2020 and 2025 were analyzed using content analysis techniques. The findings reveal a portfolio discrepancy caused by banks’ pragmatic tendency to prioritize sale-based contracts (murabahah) due to their profit certainty and risk mitigation advantages. Specifically, procedural deviations were identified in murabahah practices, including legalistic formalities (hiyal) in wakalah contracts that overlook actual ownership transfer (qabdh), as well as the potential risk of riba al-nasi'ah in debt restructuring. In contrast, profit-sharing contracts (mudharabah and musyarakah), which ideally embody the principle of risk sharing, remain marginal due to challenges associated with information asymmetry (moral hazard) and the complexity of monitoring mechanisms. The novelty of this study lies in its integrative approach, which goes beyond classical normative fiqh doctrines by providing a critical assessment of the contemporary operational realities of Islamic banking.